The method of using innovative technologies in Higher educational institutions in the context of development of the educational process: the Ukrainian reality and the European future - Kazanchuk, I. D.; Казанчук, І. Д.; Казанчук Ірина Дмитрівна (Hamilton, Ontario: Accent Graphics Communications&Publishing, 2018. - P. 227-232, 2018)
В монографічному дослідженні зазначено, що реформування та модернізація сучасної вищої освіти України у напрямку інтеграції в Європейський освітній простір передбачає розробку та впровадження інноваційних освітніх систем і технологій. Головна мета сучасної освіти в умовах інформатизації суспільства – це навчити студентів використовувати сучасні інформаційні та комунікаційні технології. Розробка та впровадження сучасних технологій потребує нових підходів до управління освітою, залучення до традиційної системи навчання принципово нових елементів, оскільки цей процес не повинен бути спрямований лише збільшення суми знань та розвиток професійної спрямованості майбутніх фахівців, але і на досягнення нової якості організації освітнього процесу, урахування сучасних підходів до організації суб’єктів професійної підготовки. Автор обов’язковою умовою використання інформаційних технологій у освітньому процесі вказав розробку нових дидактичних і методичних концептуальних засад вищої освіти. З метою ефективного їх впровадження необхідним є: створення предметно-орієнтованих навчально-інформаційних середовищ, які дозволяють використовувати мультімедіа, електроні підручники; освоєння різних засобів комунікації для обміну інформацією з опанування навчального матеріалу; навчання правил і навичок «навігації» в інформаційному просторі; розвиток дистанційної освіти.

The monographic study noted that the reform and modernization of modern higher education in Ukraine in the direction of integration into the European educational space involves the development and implementation of innovative educational systems and technologies. The main goal of modern education in the context of Informatization of society is to teach students to use modern information and communication technologies. The development and implementation of modern technologies requires new approaches to education management, involvement of fundamentally new elements in the traditional system of education, since this process should not be aimed only at increasing the amount of knowledge and the development of professional orientation of future specialists, but also at achieving a new quality of the educational process, taking into account modern approaches to the organization of subjects of professional training. The author of the necessary condition for the use of information technologies is the development of new didactic and methodological conceptual foundations of higher education defined: the creation of domain-oriented educational and information environments that allow the use of multimedia, electronic textbooks; the development of various means of communication (computer network, mobile communication) for the exchange of information with the development of educational material; learning the rules and skills of "navigation" in the information space; the development of distance education.

В монографии отмечено, что реформирование и модернизация современного высшего образования Украины в направлении интеграции в Европейское образовательное пространство предполагает разработку и внедрение инновационных образовательных систем и технологий. Главная цель современного образования в условиях информатизации общества – это научить студентов использовать современные информационные и коммуникационные технологии. Разработка и внедрение современных технологий требует новых подходов к управлению образованием, привлечения к традиционной системы обучения принципиально новых элементов, поскольку этот процесс не должен быть направлен только на увеличение суммы знаний и развитие профессиональной направленности будущих специалистов, но и на достижение нового качества организации образовательного процесса, учета современных подходов к организации субъектов профессиональной подготовки. Автор обязательным условием использования информационных технологий в учебном процессе указал разработку новых дидактических и методических концептуальных основ высшего образования. С целью эффективности их внедрения необходимо: создание предметно-ориентированных учебно-информационных сред, которые позволяют использовать мультимедиа, электронные учебники; освоение различных средств коммуникации для обмена информацией с освоение учебного материала; обучение правил и навыков «навигации» в информационном пространстве; развитие дистанционного образования.
Методика використання інноваційних технологій у вищих навчальних закладах в контексті розвитку освітнього процесу: українська дійсність та європейське майбутнє
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Монографії. Monographs; Україна. Ukraine. Украина; інформаційно-комунікаційні технології; інновації; Європейський освітній простір; інформаційний простір; дистанційне навчання; information and communication technologies; innovation; European educational space; methodology; information space; distance learning; информационно-коммуникационные технологии; инновации; Европейское образовательное пространство; информационное пространство; дистанционное обучение; вищі навчальні заклади; заклади вищої освіти; высшие учебные заведения; higher educational establishments; учреждения высшего образования; publikatsii u zarubizhnomu vydanni